Role of iNOS and eNOS expression in a group of Egyptian diabetic and nondiabetic nephropathy patients - Mayssa I. Aly; Mohamed N. Abdalla; Mohamed H.F. El Akad; Samar A.E.M. El-Sheikh; Elham M. Yousief (SpringerOpen, 2013)
Introduction and aimChanges in renal nitric oxide (NO) production have been associated with glomerular hyperfiltration, vascular permeability, albuminuria, glomerulosclerosis, and tubulointerstitial fibrosis. This study aimed at detection of the role of both inducible nitric oxide synthases (iNOS) and endothelial nitric oxide synthases (eNOS) expression in diabetic and nondiabetic nephropathy patients. MethodologyRenal biopsies and clinical data of 30 diabetic patients, 10 nondiabetic patients with renal impairment, and 10 control individuals were assessed for eNOS and iNOS expression. Results Both glomerular eNOS and iNOS expression levels were increased in diabetic nephropathy patients and this was associated with peripheral arterial occlusive disease. In nondiabetic patients, increased serum creatinine was found to be associated with increased iNOS and eNOS expression, and, together with the control group, they showed increased iNOS expression in tubular and interstitial cells. An association between cigarette smoking and increased expression of both iNOS and eNOS was detected in diabetic patients. Conclusion The presence of iNOS is associated with tubular damage resulting in renal failure. The upregulation of NO in diabetes mellitus type 2 may explain the endothelial dysfunction that is associated with almost all diabetic complications.